# 4x + 4 = 2x - 6

*print*Print*list*Cite

### 19 Answers

4x + 4 = 2x - 6

In this equation you must combine the like terms and then solve for x. First you must use inverse operations (the opposite) to move the x's and numbers to the same sides:

Subtract 2x from 2x and move it to the side of the equation with 4x + 4

4x + 4 + 2x - 2x -6

4x - 2x + 4 = -6 (What you do to one side you must do to the other side - subtract 2x from 4x)

2x + 4 = -6 (Now we must move the 4 to the other side of the equation)

2x + 4 - 4 = -6 - 4

2x = -10

Then we divide both sides by 2

x = -5

4x+4 = 2x-6

4x-2x=-6-4

2x=-10

x=-5

4x+4=2x-6

=>4x-2x=-6-4

=>2x=-10

=>x*=-5*

4x + 4 = 2x - 6

In order to solve this equation we must isolate the variable x

4x + 4 = 2x - 6

4x + 4 - 4 = 2x - 6 - 4 (subtract 4 from both sides)

4x = 2x - 10

4x - 2x = 2x -10 + 2x (subtract 2x from both sides)

2x = -10

2x/2 = -10/2 (divide both sides by 2)

**x = -5**

4x + 4 = 2x - 6

In order to solve for what x is you must put all the terms that are the alike on the same side

Now you want to know which whole number is greater and which one is less between the negative 6 and the positive 4. In this case it's -6 so we are going to add that to both sides instead of subtracting the 4 from both sides.

6+(4x + 4) = (2x - 6)+6 the 6 is going cancel out on the rights side and you'll get...

4x + 10 = 2x Now subtract 2x from 4x

2x + 10 Subtract the 2x to the right side

10 = -2x Divide 10 by -2

-5 = x There you go :D

4x + 4 = 2x - 6 subtract 2x from both sides

2x+4=-6 add 6 to both sides

2x+10=0 this is the simplified equation to get x subtract -10

2x=-10 then divide both sides by 2

x=-5

4x + 4 = 2x - 6

2x+4=-6

2x=-10

x= -5

4x + 4 = 2x - 6

4x + 4 = 2x - 6

[4x - 2x] + 4 = -6 **First get the variable on the same side**

2x+4 = -6 **Subtract +4 from both sides**

2x = -10 **Divide 2 from both sides**

x = -5

4x + 4 = 2x - 6

To solve this equation, first subtract 2x on both sides, this way the " x " would all be on the same side making this equation easier to solve.

Once you subtract 2x on both sides your equation should be

**2x + 4 = -6** Now subtract four from both sides

After subtracting four from both sides your equation should be

**2x = -10 **Now divide 2 from both sides

After dividing 2 from both sides your equation should be

**x = -5 **which is your answer

# 4x + 4 = 2x - 6

2x +4= -6 subtract 2x

2x=-10 subtract 4

x= -5 divide by 2

4x + 4 = 2x - 6

Combine like terms. You want your variables on one side and your numbers on the other. In this case, I subtracted 2x from both sides to get my x terms all on the same side. I subtracted 4 from both sides to get my numbers all on the other side:

2x = 10

We have to undo whatever is being done to the variable to solve for it. The opposite of multiplication is division so I will divide both sides by 2.

x = 5

4x+4=2x-6

4x+4-2x=2x-6-2x

2x+4=-6

2x+4-4=-6-4

2x=-10

x=-5

4x + 4 = 2x - 6

(4x-2x) +4 = -6

2x+4=-6

2x+4=(-6-4)

2x= -10

x= -5

4x+4=2x-6

4x+4-4=2x-6-4

4x=2x-10

4x-2x=2x-10-2x

2x=-10

2x/2=-10/2

x=-5

Move the x's to one side of the equal sign and move the numerals to the other side of the equal sign.

2x = -10

x = -5

You can also email my teacher for help at helpmathtutor@gmail.com

4x + 4 = 2x - 6

4x-2x=(-6)-4

2x=-10

x=(-5)

The method in the answer posted above is correct. However there is a simpler and shorter method of getting all the terms containing x on left hand side and all the terms containing only number on the right hand side of the equation. The rule is that you can shift any term in an equation from one side to the other by simply changing the sign of the term. Thus, when terms are shifted from one side to another the terms with positive signs will acquire negative sign, and terms with negative sign will acquire positive signs. The alternate solution using this method is given below>

Given 4x + 4 = 2x - 6

Therefore shifting all terms containing x to left hand side and only numbers to right hand side of equation we get:

4x - 2x = - 6 - 4

Therefore: 2x = -10

Therefore: x = -10/2 = -5 Answer

To solve 4x+4=2x-6.

This is a simple equation in one unknown (or variable x). We have to find the value of the unknown x.

We employ a technic of shifting all the unknowns, i.e. x's to the left and all the knowns or the numbers to the right, by simple operations like adding equals to both sides, or subtracting equals from both sides , or multiply by equals both sides , or dividing by equals both sides,(except dividing by zero) .

Subract 2x from both sides.

4x+4**-2x**= 2x-6**-2x**

Simplify by collecting the like terms, 4x and -2x on the left which gives 2x. On the right 2x and -2x are the like terms and they get cancelled.

2x+4=-6

Subtrat 4 from both sides:

2x+4**-4**=-6**-4.**

Simplify both sides:

2x=-10.

Divide both sides by 2

2x**/2**=-10**/2.**

Simplify both sides.

x=-5.

Verification: Substititute the solution x=-5 in the given equation and see whether both sides become equal in value:

Left side : 4x+4= 4*(-5)+4=-20+4=-16

Right side:2x-6=2*(-5)-6 = -10-6=-16.